Hydroporus golestanensis, a new species of the H. longulus group from northern Iran (Coleoptera: Dytiscidae: Hydroporinae) - Hájek, Jiří (Zootaxa, 2016)
Hydroporus golestanensis sp. nov. from Golestan Province, Iran, is described and illustrated. Based on the distinctly sinuate posterior margin of the metacoxal processes, the new species belongs to the H. longulus species group. Hydroporus golestanensis sp. nov. can be recognised from all the other species in the group by the pitchy-brown colouration of the elytra and by the almost symmetrical male median lobe, with distal third evenly tapering to a pointed apex in ventral view.